2015
DOI: 10.1007/s12020-015-0640-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that non-alcoholic fatty liver disease and polycystic ovary syndrome are associated by necessity rather than chance: a novel hepato-ovarian axis?

Abstract: Increasing evidence suggests that non-alcoholic fatty liver disease (NAFLD) and polycystic ovary syndrome (PCOS) are associated with obesity, insulin resistance, metabolic syndrome, cardiovascular disease, cirrhosis, and liver tumors. On these grounds, we have hypothesized that NAFLD and PCOS occur more frequently than expected by chance alone. We have tested this hypothesis by reviewing the clinical and biological evidence that supports a significant association between NAFLD and PCOS. PubMed was extensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 87 publications
0
56
0
7
Order By: Relevance
“…Most of these studies support the assertion that CVD is the most common cause of mortality among patients with NAFLD. This [2,9,37].…”
Section: Nafld and Cvdmentioning
confidence: 92%
See 1 more Smart Citation
“…Most of these studies support the assertion that CVD is the most common cause of mortality among patients with NAFLD. This [2,9,37].…”
Section: Nafld and Cvdmentioning
confidence: 92%
“…Despite emerging evidence suggests that NAFLD is also linked to other chronic diseases [7][8][9][10], it is the adverse impact of NAFLD on CVD risk which deserves particular attention owing to the epidemics of obesity/MetS leading to a dramatic surge in the proportion of NAFLD patients in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed that women with PCOS have a four times higher risk of NAFLD in comparison to healthy women (116). NAFLD is usually considered as a hepatic manifestation of MetS (117); however, some studies confirmed that PCOS women without concomitant MetS and obesity have a higher prevalence of NAFLD in comparison to healthy women (57,58,118). Taking into account the fact that women with PCOS are young and that they might already have NASH, it follows that a high risk of liver-related comorbidities and complications could extend from reproductive to menopausal age.…”
Section: Prevalence Of Nafld In Pcosmentioning
confidence: 99%
“…Special emphasis is conferred to CVD risk. The relationship of polycystic ovary syndrome (PCOS) to NAFLD has recently been covered elsewhere [32] and is outside the scope of this review.…”
Section: Introductionmentioning
confidence: 99%